Development and Evaluation of a Virtual Reality-Based Mandarin Language Learning System Enriched with Chinese Cultural and Geographical Contexts - Rizaldi Eko Prasetyo; Esther Irawati Setiawan; Joan Santoso (Teknika, 2025)
In Junior High School Sepuluh Nopember Sidoarjo has a superior program, namely International Class, in this type of class there is Mandarin learning. However, in reality, students who take junior high school have low language skills, especially in Mandarin. Because conventional learning materials tend to be boring for students. The purpose of this study is to improve students' understanding of the use of Virtual Reality technology in learning Mandarin. The method used in this study is using Experimental Design (Pretest-Posttest Control Group Design) and uses the N-Gain test theory. After testing using this method, the results obtained were an increase in learning outcomes of 22% from learning that initially used conventional learning to learning based on Virtual Reality technology. This increase indicates that the use of Virtual Reality (VR)-based learning media has a positive impact on improving students' understanding of the material being studied.